Antibakteri Ekstrak Etanol Daun Jambu Biji (Psidium guajava L.) Terhadap Escherichia coli - Rahmiati Rahmiati (Herbal Medicine Journal, 2019)
Psidium guajava L. is a plant that is widely used and cultivated throughout Indonesia which has a potential as a medicinal plant. The leaves from Psidium guajava L. had been studied and were known the contain secondary metabolites with antibacterial activity, namely flavonoids and tannins. In this study, the antibacterial activity of Psidium guajava L. leaves were tested against Escherichia coli bacteria. The objective of this study was to determine the antibacterial activity of %96 ethanol extracts of Psidium guajava L. leaf against Escherichia coli bacteria. The Psidium guajava L. leaves extracts were prepared by maceration method using % 96 ethanol as solvents. The macerate was evaporated give thick extract. The concentrations of extracts used for the treatment group were 500 mg/ml, 250 mg/ml, 100 mg/ml, 50 mg/ml, 30 mg/ml, 20 mg/ml, 10 mg/ml. Disc diffusion method was used to measure the bacterial inhibition zone and to determine the minimum inhibitory concentration (MIC). The Results of activity %96 ethanol extract of Psidium guajava L. leaf can inhibit the growth of, Esherichia coli bacteria at a concentration of 25 mg/ml with the diameter of inhibition zone 6.88 mm.